On the Merge sites of Dutch perception verbs - van Craenenbroeck, Jeroen; van Koppen, Marjo (Nordlyd, 2026)
This paper investigates the syntactic distribution of Dutch perception verbs and argues that their different uses correspond to distinct Merge positions in the clausal spine. Focusing on verbs such as horen ‘hear’ and kijken ‘look’, we distinguish four types: fully lexical perception verbs, ECM-perception verbs, inflected imperatives in dialect Dutch, and perception verbs used as discourse markers. These uses form a cline from lexical to functional status. Evidence for the higher Merge positions comes from a comparison of regular imperatives, inflected imperatives, and discourse-marker uses, evaluated against criteria such as semantic bleaching, argument structure, class size, and morphological defectiveness. Evidence for the lower Merge positions comes from corpus-based ordering and co-occurrence patterns involving perception verbs and auxiliaries, modals, causative verbs, motion verbs, posture verbs, and passive auxiliaries. We propose that ECM-perception verbs are merged in a specialized v-position associated with perceptionand causation, while discourse-marker uses occupy the speech-act layer.
Keywords: Dutch; perception verbs; grammaticalization